Individual and combined contributions of non-high-density lipoprotein cholesterol and brachial-ankle pulse wave velocity to cardiovascular disease risk: Results of a prospective study using the Kailuan cohort - Zheng, Qiongbing; Wang, Hui; Wang, Xianxuan; Lan, Youmian; Wu, Weiqiang; Yu, Xinran; Huang, Zegui; Chen, Zekai; Cai, Zefeng; Lin, Qi; Zhou, Houshi; Zhu, Yongdong; et al. (Frontiers in Cardiovascular Medicine, 2023)
Objective We aimed to characterize the relationship of a combination of circulating non-high-density lipoprotein-cholesterol (non-HDL-C) concentration and brachial-ankle pulse wave velocity (baPWV) with cardiovascular disease (CVD). Methods We performed a prospective cohort study of the residents of the Kailuan community, with data from a total of 45,051 participants being included in the final analysis. The participants were allocated to four groups according to their non-HDL-C and baPWV status, each of which was categorized as high or normal. Cox proportional hazards models were used to explore the relationships of non-HDL-C and baPWV, individually and in combination, with the incidence of CVD. Results During the 5.04-year follow-up period, 830 participants developed CVD. Compared with the Normal non-HDL-C group independently, the multivariable adjusted hazard ratios (HRs) and 95% confidence intervals (CIs) for CVD in the High non-HDL-C was 1.25 (1.08–1.46). Compared with the Normal baPWV group independently, the HRs and 95% CIs for CVD in the High baPWV was 1.51 (1.29–1.76). In addition, compared with the Normal both non-HDL-C and baPWV group, the HRs and 95% CIs for CVD in the High non-HDL-C and normal baPWV, Normal non-HDL-C and high baPWV, and High both non-HDL-C and baPWV groups were 1.40 (1.07–1.82), 1.56 (1.30–1.88), and 1.89 (1.53–2.35), respectively. Conclusion High non-HDL-C concentration and high baPWV are independently associated with a higher risk of CVD, and individuals with high both non-HDL-C and baPWV are at a still higher risk of CVD.